(3CfhGY fXe GdeYdheGJ aj GdefXeGJ (B- (3GdJYde GdJfXjej hEOGQI GdeYQaI (B- (3EJNGP GdbQGQGJ GdfXe GdCOhGJ (B- (3bhGYO GdHjGfGJ hESJNHGQGJ GdCYeGd(B.s - (3ZGOI YHO GdhgGH(B, (3GdNjGWs ((3GdEScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s)
(3JWQb gPG GdcJGH Gdi ehVhY fXe JcfhdhLjG GdeYdheGJ, MjK JMOK Yf CfhGY fXe GdeYdheGJ aj GdefXeGJ hYf GdJYde GdJfXjej hEOGQI GdeYQaI, HGdGVGaI Gdi EJNGP GdbQGQGJ h GdfXe hGdCOhGJ , hCNjQG Je GdMOjK Yf bhGYO GdHjGfGJ hESJNHGQGJ GdCYeGd(B.s
(3HHdjhZQGajG U(B.319s
Keywords: (3JcfhdhLjG GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s